2019
DOI: 10.1111/1755-0998.12967
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of connectivity in populations of a semi‐aquatic mammal using kinship categories and network assortativity

Abstract: Analysing the impact of anthropogenic and natural river barriers on the dispersal of aquatic and semi‐aquatic species may be critical for their conservation. Knowledge of kinship relationships between individuals and reconstructions of pedigrees obtained using genomic data can be extremely useful, not only for studying the social organization of animals, but also inferring contemporary dispersal and quantifying the effect of specific barriers on current connectivity. In this study, we used kinship data to anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
49
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 89 publications
(136 reference statements)
2
49
0
Order By: Relevance
“…Additionally, the concatenation of smaller artificial barriers as well as ecological barriers resulting from contamination and predation by invasive species in the lower parts of rivers, has confined many desman populations to the river headwaters over the past few generations (Quaglietta et al 2018). The consequence of this isolation is that desmans can only breed with other individuals of the same river, which are usually closely related as determined through relatedness networks (Escoda et al 2017;Escoda et al 2019). This, in turn, leads most desmans to have high inbreeding levels (Escoda et al 2017).…”
Section: Lessons From the Genome Of A Species With Extraordinary Inbrmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the concatenation of smaller artificial barriers as well as ecological barriers resulting from contamination and predation by invasive species in the lower parts of rivers, has confined many desman populations to the river headwaters over the past few generations (Quaglietta et al 2018). The consequence of this isolation is that desmans can only breed with other individuals of the same river, which are usually closely related as determined through relatedness networks (Escoda et al 2017;Escoda et al 2019). This, in turn, leads most desmans to have high inbreeding levels (Escoda et al 2017).…”
Section: Lessons From the Genome Of A Species With Extraordinary Inbrmentioning
confidence: 99%
“…A ddRADbased study on the species revealed extremely low heterozygosity in some individuals from the eastern Pyrenees, probably as a consequence of repeated bottlenecks during the postglacial recolonization of these mountains (Querejeta et al 2016). In addition, it has been demonstrated that the isolation of populations in the upper parts of rivers due to the construction of artificial barriers, such as dams, is leading to extremely high inbreeding levels in some areas (Escoda et al 2017;Escoda et al 2019). Having the complete genome of the Pyrenean desman would allow us to study how the combination of strong population bottlenecks and high inbreeding levels is reflected in the genomic landscape of a threatened species.…”
Section: Introductionmentioning
confidence: 99%
“…Escoda, Fernández‐González, and Castresana () represent a step forward in kinship‐based methods as it uses a statistical framework that develops “null” models of the expected distribution of kin relationships between two groups under random mixing. The authors use the assortativity coefficient (AC), which has been used in network analysis to study preferential associations in human social networks (Newman, ).…”
mentioning
confidence: 99%
“…Pyrenean desman ( Galemys pyrenaicus ; centre right) and the barriers to its dispersal found using kinship and network analyses in Escoda et al (). The upper panel shows the watershed divide between the Tuela and Tera rivers in Zamora (Spain) that was a natural barrier to dispersal.…”
mentioning
confidence: 99%
See 1 more Smart Citation